Lexical Errors Produced by High And Low Proficiency Learners of Writing 2 Classes - Ellara Yusea Ananda; Henny Putri Saking Wijaya (Kata Kita: Journal of Language, Literature, and Teaching, 2021)
This study was conducted to find out the types of lexical errors that high and low proficiency learners produced in their writing, and find the differences and similarities from the production of the two groups. To answer the research questions, the writers used the theory by James (2013) about lexical error classification. This study was a qualitative study. The sources of the data of this study were the lexical errors from 32 writing drafts. The writers divided the students into two groups: eight students from high proficiency level and eight students from low proficiency level. The findings showed that the high proficiency learners produced five types of formal errors and four types of semantic errors, while the low proficiency learners produced two types of formal errors and six types of semantic errors. In conclusion, the high and the low proficiency learners’ lexical error productions are due to the learners’ lack of knowledge in sense relation and collocation, and the learners’ wrong terms of near-synonyms production.Keywords: lexical errors, high proficiency learners, low proficiency learners, error analysis